Floods in South Asia - Dixit, Ajaya (Water Nepal, 2009)
Ajaya Dixit's paper deals with floods in South Asia. He argues that if one move away from the structural flood control and disaster relief activities that charaterise conventional approaches to flood mitigation and focus more on the root caused of vulnerability the points of leverage for mitigating disaster that could prove more effective. Key words: Floods; flood mitigation; disaster relief; South Asia Water Nepal Vol. 12, No. 1&2, 2006 Page: 207-226